Pengaruh Capital Expenditure, Corporate Hedging, Struktur Modal, dan Profitabilitas Terhadap Nilai Perusahaan Pada Masa Pandemi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Faradiba; Hidayat, Taufik (Asosiasi Dosen Akuntansi Indonesia, 2024)
The aim of this research is to determine the magnitude of the influence of Capital Expenditure, Corporate Hedging, Capital Structure and Profitability on Company Value During the Pandemic (Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange 2020-2021). This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2021 period. The data collection technique in this research used a purposive sampling technique so that the total sample was 142 samples. The research results show that Capital Expenditure has no effect on company value. Corporate Hedging, Capital Structure and profitability influence company value